STRATEGI PENGEMBANGAN QUALITY TOURISM PADA OBJEK WISATA GUCI SEBAGAI POTENSI PERTUMBUHAN EKONOMI DAERAH - Khamidah, Khilfatul; Azakia, Kiki (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
The development of tourism destinations has good prospects and can be relied upon to support and contribute to regional income through levies, one of which is the Guci tourist destination located in Tegal Regency, Central Java Province. Guci has various natural potentials and is supported by an agrarian society. The condition of Guci tourism this year has experienced a decline due to the accident of a tourist bus from the city of Tanggerang on May 7 2023. The cause is limited management capacity due to lack of government and private cooperation, lack of involvement of the community in developing Guci tourism, damage to nature and the impression of being dirty, limited facilities and supporting infrastructure such as damaged or narrow roads and unstrategic parking, inadequate modes of transportation and several irresponsible individuals. This research aims to analyze what quality tourism development strategies will be applied to Guci tourism so that it provides competitive value for Tegal Regency. The research method uses descriptive qualitative analysis with classification and development trends to determine the condition of tourism products and markets. The results of the research show that there are at least three supporting aspects that can be important in quality tourism, especially to fulfill aspects of quality tourism, namely quality of experiences, quality of profile, and quality of life. Keywords: strategy, development, quality tourism, urn tourist attraction